Distributional evidence and threats to cheer pheasant (Catreus wallichii) in Annapurna Conservation Area, Nepal - Chhetri, Nar Bahadur; Dhami, Bijaya; Neupane, Bijaya; Sadadev, Bipana Maiya; Thapa, Nabaraj (Nepalese Journal of Zoology, 2020)
Cheer pheasant, a vulnerable species in the pheasant family, Phasianidae, is found distributed through the southern foothills of the Himalayas from Pakistan to Nepal. In Nepal, it has been recorded from few areas including the Annapurna Conservation Area (ACA) in central Nepal. However, no systematic survey has been conducted on this shy species in the ACA since 2010. Thus, this study represents a general picture of cheer pheasant distribution and potential threats in Lete and Kunjo Rural Municipalities of Mustang district within the ACA by establishing vantage points in different locations. Among ten vantage stations, cheer pheasants were detected from all stations in Kunjo but only from three stations in Lete. The major threats to the species were found to be overgrazing, habitat fragmentation and hunting/snaring. For the effective conservation of cheer pheasants, a conservation program should be promptly formulated and implemented in Mustang district.